Model of family health empowerment preventing stroke in Puskesmas Ulee Kareng Banda Aceh. (February 2020) - Marlina',; Badaruddin,; Fikarwin, Z; Lubis, R
Abstract: Stroke is a clinical sign that develops from the Focal brain with symptoms that occur for a day or more and can cause death for no apparent reason other than vascular. Stroke has become the leading cause of death in almost all hospitals in Indonesia and in Aceh is the number one death factor. The purpose of this study is to empower families to get a stroke prevention model and have the effect of that model for lowering blood pressure, cholesterol and blood sugar. Participants in this study were hypertension sufferers with a total of 32 participants at the Ulee Kareng Health Center in Banda Aceh. The study was conducted from February 2017 to December 2018, using the Participatory Action Research (PAR) and T-Test methods. The results of research through PAR studies found stroke prevention models and differences in blood pressure, cholesterol and blood sugar decreased after the study. It can be concluded that the effect of the stroke prevention model was found to reduce the risk of stroke. Recommendations: Strengthening and family motivation is very influential to reduce the risk of stroke.